Development of Language Awareness Scale regarding Daily Life - İsmail Karakaya; Mustafa Erol (International Journal of Assessment Tools in Education)
The aim of this study is to develop the language awareness scale regarding daily life. The study group consisted of 606 undergraduate students studying at a university in Istanbul. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used in the study. EFA result indicates that the scale consists of 17 items and 4 factors and 67% of the total variance is explained. Factors were named as Individual Awareness, Social Media Awareness, Awareness Regarding Daily Life and Awareness in the Mass Media. As a result of the CFA, it was determined that the scale had 17 items and the fit indices of the structure were sufficient (χ2 / sd = 2.54, RMSEA = 069, SRMR =.07). Item-total correlations of the scale were found to range between 79 and 89. Cronbach Alpha internal consistency coefficient of the scale was found to be as 86. Based on these findings, it can be said that the scale can be used in a valid and reliable way to measure students' language awareness about daily life.